(untitled) (Revista de Ensino em Artes, Moda e Design, 2024)
The aim of this study was to develop braided fibrous structures for scaffold implant applications, utilizing graphical simulation with Rhinoceros 3D® software (version 6) and the Grasshopper plugin. The research aimed to emphasize key aspects of woven textile structures and support textile design education. To achieve these goals, the study proceeded through two stages. Stage 1 involved an exploratory-descriptive phase with a brief literature review, while Stage 2 comprised applied qualitative and descriptive research. Morphological analyses of the braided structures indicated that the average interlacing angle was consistently influenced by wire diameter, number of wires, orientation, applied tension, material, and structure diameter. These findings align with existing literature and underscore the significance of graphic simulation and advanced software in advancing both the development and pedagogy of textile design.